PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN SUMBER KEARIFAN LOKAL MENJADI PRODUK UNGGULAN MELALUI PERAN KKN TEMATIK BERBASIS MASJID DESA BANGUNSARI SONGGON - Nurul Fatimah (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2019)
Every village needs to see what sectors or commodities have great potential and can be developed quickly. In order for products that are produced by a village based on the potential and superiority of the village, the products produced by the village must be able to compete with products from other villages. Community Empowerment through the Utilization of Local Wisdom Sources into Featured Products through the Role of Mosque-Based Thematic KKN in Bangunsari Songgon Village is carried out through economic empowerment in the form of: 1) Training on Making VCO (virgin coconut oil); and 2) Coffee Pie Making Training. The identification of problems in the implementation of this service uses a participatory rural appraisal (PRA) model. From the results of the training given to the Bangunsari Songgon village community, the community welcomed very well because they were able to receive new knowledge and the right marketing strategies of potential crops in their area.